Digital Beamforming for a Secondary Surveillance Radar: Numerical and statistical analysis of the ADS-B reception performance for an SSR system with conventional and adaptive beamforming - Wiklund, Mattias (My University, 2024)
A secondary surveillance radar (SSR) is a surveillance radar system which, rather than detecting reflected signals, relies on interrogations and replies to identify targets. In this master’s thesis, the performance of an SSR system is analyzed. The performance is measured by estimating the probability to detect Automatic Dependent Surveillance-Broadcast (ADS-B) signals interfered by other signals on the 1090 MHz frequency band. The study is performed using different beamforming techniques, with the aim of enhancing the reception in some directions while reducing it in others. The probability of detection is estimated by performing Monte Carlo simulations for different target positions and interference scenarios. Simulations are performed for a system using digital beamforming, individually digitizing the received signal in the different antenna elements in the SSR. Both conventional beamforming, using a fixed set of beam positions, and adaptive beamforming, using properties of the received data to optimize the reception, is analyzed. This is benchmarked against a system using analog conventional beamforming, where the signals are decoded in either a sum or a difference channel. The results of this study highlight the potential of digital beamforming, significantly increasing the probability of detection compared to the analog system, especially in an environment with large amounts of interfering signals. Among the adaptive algorithms tested, linear constraint minimum power (LCMP) beamforming, imposing null constraints on interfering signals, exhibited the most promising results. There is potential to build on this work, further analyzing the applicability of the different beamforming techniques. Future research areas could include analyzing more adaptive algorithms, as well as optimizing the ones studied in this thesis.
Keywords: Secondary surveillance radar, ADS-B, Conventional beamforming, Adaptive beamforming, Statistical signal processing, Monte Carlo simulations.